MOVIMENTO DE MULHERES E FEMINISTAS E SUA AÇÃO ANTICAPITALISTA NO BRASIL E MARANHÃO - Mary Ferreira (Revista de Políticas Públicas, 2014)
The Feminism action in Brazil which has as mark the seventies, when this movement spread through several Brazilian states, bringing to society the perspective of women, to build a society without gender relations, in which women could share equal spaces of power and have their rights respected. In this context, this article shows that, although the fight over the last forty years has contributed to major changes, it is still observed the almost exclusive responsibility of women with the housework. Shows that, there is still exclusion in politics, when studies indicate a presence of only 13% of women in Brazilian legislative, exclusion that is also observed in secondary jobs and low wages, which demonstrates that, capitalism articulates with the patriarchate in order to devalue women workforce, imputing undervalued and underpaid positions. This fact reflects the sexual division of labor that created divisions between productive and reproductive work, segregating women in jobs that reinforce gender relations and their exclusion from public life.